The effect of recurrent pregnancy loss on obstetric and neonatal outcomes: a systematic review and meta-analysis - Yunyan Chen; Boliang Chu; Yingying Chen (The Journal of Maternal-Fetal & Neonatal Medicine)
Objective To provide comprehensive evidence on the impact of prior recurrent pregnancy loss (RPL) on obstetric, perinatal, and neonatal outcomes.Methods PubMed, EMBASE, and Scopus databases were screened for observational cohort, case-control, and cross-sectional studies in peer-reviewed journals. Pooled effect estimates were calculated by random-effects models and reported as an odds ratio (OR) with 95% confidence intervals (CIs).Results The study included 14 papers. Most of the studies (n = 12) were retrospective. Women with previous RPL had higher risk of pre-eclampsia (OR 1.25, 95% CI: 1.04, 1.50), placental abruption (OR 2.11, 95% CI: 1.31, 3.39), and delivery through cesarean section (OR 1.41, 95% CI: 1.21, 1.65) than women with no prior pregnancy loss. Women with previous RPL also had an increased risk of still birth (OR 1.77, 95% CI: 1.19, 2.61), preterm birth (OR 1.58, 95% CI: 1.38, 1.81), child born small for gestational age (SGA) (OR 1.31, 95% CI: 1.11, 1.55) and perinatal mortality (OR 2.02, 95% CI: 1.46, 2.81). The risks of having a neonate with low birth weight (<2500 g at birth), APGAR score of less than 7 (at 5 min), and requiring neonatal intensive care unit admittance were somewhat higher in women with previous RPL. There was no significant correlation between the history of recurring miscarriage and gestational diabetes and birth defects. The certainty of evidence was “low” to “very low” for most of the outcomes considered.Conclusions RPL was associated with a higher risk of negative obstetric and neonatal outcomes, such as pre-eclampsia, placental abruption, cesarean section, stillbirth, and SGA.